2012
DOI: 10.1080/14733145.2012.656136
|View full text |Cite
|
Sign up to set email alerts
|

Adult survivors' of childhood sexual abuse perspectives of services: A systematic review

Abstract: Aims: This review summarises and evaluates evidence regarding psychotherapy/counselling services for childhood sexual abuse (CSA) from the survivors' perspective. Methods: Studies were identified from systematic literature searches of PubMed, PsycINFO, CINAHL, Psychology and Behavioural Sciences Collection. Selected studies were published in English after 1980. Results: Nine studies met the inclusion criteria for this review. Survivors identified a range of experiences of services. Positive experiences focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The need for models of recovery from CSA which capture the dynamic and relational aspects of the change process in adulthood has been highlighted before (Chouliara et al, 2014; Chouliara et al, 2012; Saunders, 2003; Williams, 2003). The findings of the present study bear significance, which extends to a clinically meaningful understanding of relational processes in group therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The need for models of recovery from CSA which capture the dynamic and relational aspects of the change process in adulthood has been highlighted before (Chouliara et al, 2014; Chouliara et al, 2012; Saunders, 2003; Williams, 2003). The findings of the present study bear significance, which extends to a clinically meaningful understanding of relational processes in group therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Olio suggests the establishment of an effective therapeutic relationship "is probably the single most important factor" in the successful treatment of adult sexual abuse survivors (1989, p.98). Consequently, as a result of the particular relational difficulties CSA survivors can experience, it is important to understand how survivors experience talking therapies (Chouliara et al, 2012).…”
Section: How Do Adult Survivors Of Childhood Sexual Abuse Experience Formally Delivered Talkingmentioning
confidence: 99%
“…In terms of therapeutic modality, CSA survivors have, in some studies, reported that the type of therapy they have received has not influenced whether therapy itself was beneficial (Chouliara et al, 2012;Hetzel-Riggin, Brausch & Montgomery, 2007;Nelson & Phillips, 2001). Moreover, a recent meta-synthesis (Draucker et al, 2009) exploring healing for sexual violence survivors concluded that it was understanding experiences, rather than developing positive or adaptive coping strategies, which survivors found helpful.…”
Section: How Do Adult Survivors Of Childhood Sexual Abuse Experience Formally Delivered Talkingmentioning
confidence: 99%
“…[38] Trust has also been shown to be central to recovery from CSA in adulthood both within and without mental health services, as well as a sign of recovery. [44][45][46] Trust has also been shown to be an important factor in survivors' satisfaction with mental health services. [47] CSA is associated with negative impacts on the stability and quality of intimate relationships in adulthood.…”
Section: Introductionmentioning
confidence: 99%